2017
DOI: 10.1038/s41598-017-14054-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived laser-induced arc discharges for energy channeling applications

Abstract: Laser filamentation offers a promising way for the remote handling of large electrical power in the form of guided arc discharges. We here report that it is possible to increase by several orders of magnitude the lifetime of straight plasma channels from filamentation-guided sparks in atmospheric air. A 30 ms lifetime can be reached using a low-intensity, 100 mA current pulse. Stability of the plasma shape is maintained over such a timescale through a continuous Joule heating from the current. This paves the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Since the time and space of discharges can be accurately controlled, many applications based on laser-induced filament were developed [185,186]. Polynkin et al [187] reported a multi-pulse scheme for laser-guided electrical breakdown of air, which is shown to be suitable for guiding discharges propagating in either direction or along curved paths.…”
Section: Femtosecond Lasers Guided High Voltage Electric Dischargesmentioning
confidence: 99%
“…Since the time and space of discharges can be accurately controlled, many applications based on laser-induced filament were developed [185,186]. Polynkin et al [187] reported a multi-pulse scheme for laser-guided electrical breakdown of air, which is shown to be suitable for guiding discharges propagating in either direction or along curved paths.…”
Section: Femtosecond Lasers Guided High Voltage Electric Dischargesmentioning
confidence: 99%
“…Femtosecond filament triggered HV discharges have been widely studied in recent years, with applications envisioned to include reconfigurable RF antennas and guiding of electrical pulsed power, including lightning [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%